Cutaneous Manifestations and Their Corresponding Dermoscopic Features in Patients with Dermatomyositis - Joana Pozharashka; Ljubka Miteva; Lyubomir Dourmishev (Mattioli1885, 2022)
Introduction: Dermoscopy is a noninvasive and easy to apply technique that allows in vivo magnification of the skin and thus observation of morphologic structures invisible to the naked eye. Recently, it gained popularity for evaluation of inflammatory skin conditions. In the field of connective tissue diseases, dermoscopy has been used mainly as a simple and accessible substitute of nailfold capillaroscopy. Objectives: The aim of the present study is to expand the application of dermoscopy in patients with dermatomyositis (DM) beyond the usual nailfold examination. A clinico-dermoscopic correlation is also suggested. Methods: A total of twenty-nine patients with DM were enrolled in this descriptive prospective study, conducted over a three-year period. Dermoscopy was performed by a DermLite DL1 dermatoscope on polarization mode, attached to One Plus 3T camera. The following skin lesions were examined - periungual affection, scalp DM, Gottron's papules, palmar papules, poikiloderma and auricular changes. Results: Dermoscopy detected predominantly advanced nail fold capillary changes - giant capillaries (79%), microhemorrhages (46%) and avascular areas (25%). The most prevalent trichoscopic features were enlarged tortuous capillaries (64%), interfollicular scales (50%) and peripilar casts and tufting (36%). Among the other skin lesions assessed in this study - Gottron's papules were present in 20 patients, poikiloderma in 11, palmar papules in 4 and auricular lesions in 4 patients.